Quality of Life among Stroke Survivors - Lalu, Litty Vadakkethil; Moly, K.T.; Thomas, Priya (RA Journal of Applied Research, 2021)
The physical and cognitive sequelae resulting in functional disabilities after Stroke has an influence on the quality of life (QoL) of stroke survivors. The objective of the study was to assess stroke specific quality of life among stroke survivors. A Quantitative descriptive study in which 50 stroke survivors attending the stroke OPD of a tertiary care hospital after a month were taken using convenient sampling. Their Quality of Life (QoL) was assessed in 12 domains using Stroke Specific Quality of Life (SS-QOL). The Data was analyzed using descriptive and inferential statistics. A fairly good QoL was seen among the study subjects. The mean SS-QOL was 174.86 with a SD of +/- 46.81 in a maximum score of 245 (71.37%). The most affected domain in SS-QOL was social role (59.36%), followed by family role (61.72%) and the least affected were vision (82.26%) and language (86.24%). The poor QoL in social roles and family roles clearly indicates the necessity to strengthen the stroke rehabilitative services in our community.